Military Means for Non-Military Measures: The Russian Approach to the Use of Armed Force as Seen in Ukraine. Issue 4 (1st October 2016) - Westerlund, Fredrik; Norberg, Johan
ABSTRACT: The Russian Federation's approach to the use of armed force abroad is a concern for other states. This case study of Russian armed force use against Ukraine in 2014 and 2015 employs an analytical framework based on Russian conceptualizations. Distinguishing between military and non-military means and measures, we analyze Russia's deployment of armed forces to carry out measures in interstate conflict resolution, focusing on military forces deployed for non-military measures. We find that the use of armed forces in Ukraine largely conforms to Russian conceptualizations, allowing for extensive fighting without it amounting to a military conflict in the Russian view.